Transurethral Inlay Vaginal Graft Urethroplasty for Female Urethral Stricture - Allen, Naomi Constantia; Nababan, Parsaoran; Ramadhan, Raden Dadan Mochamad; Yance, Fedry (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2024)
Introduction. Female urethral stricture is rare. Treatment option includes urethroplasty with various techniques, but no single approach has been demonstrated to be the best. One major issue has been the risk of post operative incontinence.Case. We present our experience of the management of female urethral stricture with transurethral inlay vaginal graft urethroplasty. A 51 year old female patient presented with urinary retention and foley insertion failed. Urethroscopy showed panstricture of the urethra and transurethral inlay urethroplasty was performed using vaginal graft. The patient showed improvement of the symptoms postoperatively.Conclusion. Transurethral inlay urethroplasty is a feasible option for the management of female urethral stricture to reduce the risk of post op incontinence because it doesn’t require high urethral mobilization.